2020
DOI: 10.1007/s10811-020-02299-7
|View full text |Cite
|
Sign up to set email alerts
|

Production of exopolymer substances from the thermophilic chlorophyte Graesiella: industrial and ecological applications

Abstract: Microalgal extracellular polymeric substances (EPSs) are heteropolysaccharides that have characteristics suitable for industrial and biotechnological applications. Notably, they have strong anionic nature and high hydrophobicity. Nevertheless, systematic studies to demonstrate the viability of the production of EPSs on an industrial scale are still crucial. In this research, the chlorophyte Graesiella was grown on a raceway pond to view its EPS valorization. The biomass production achieved a maximum of 1.98 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…In a previous work [13], results showed that Graesiella sp., is found amongst the most efficient EPSs producers reaching values close to 1.62 g⋅L − 1 in laboratory cultures. The native Graesiella sp., EPS are hetero-sulphated polysaccharides of anionic nature composed mainly with polysaccharides (80%) and proteins (14%), presenting a high crystalline nature.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…In a previous work [13], results showed that Graesiella sp., is found amongst the most efficient EPSs producers reaching values close to 1.62 g⋅L − 1 in laboratory cultures. The native Graesiella sp., EPS are hetero-sulphated polysaccharides of anionic nature composed mainly with polysaccharides (80%) and proteins (14%), presenting a high crystalline nature.…”
Section: Introductionmentioning
confidence: 89%
“…The strain was isolated from a hot-spring (60 • C; North of Tunisia at 36 • 49 ′′ N, 10 • 34 ′′ E) and grown in Bold's Basal Medium (BBM) at a temperature of 30 ± 1 • C and a light intensity of 120 μmol photons m − 2 s − 1 . Extracellular Polymeric Substances (EPS) were extracted from a stationary phase culture as described by Gongi et al [13]. The recovered EPS solution was freeze-dried and stored in dark and dry conditions for edible film preparation.…”
Section: Strain and Extracellular Polymeric Substances Isolationmentioning
confidence: 99%
See 3 more Smart Citations